2022
DOI: 10.3389/fimmu.2022.1050876
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risks in rheumatoid arthritis patients who received immunosuppressive therapies: Will immunosuppressants work?

Abstract: BackgroundExploring the cancer risks of rheumatoid arthritis (RA) patients with disease-modifying anti-rheumatic drugs (DMARDs) can help detect, evaluate, and treat malignancies at an early stage for these patients. Thus, a comprehensive analysis was conducted to determine the cancer risk of RA patients using different types of DMARDs and analyze their relationship with tumor mutational burdens (TMBs) reflecting immunogenicity.MethodsA thorough search of PubMed, EMBASE, Web of Science, and Medline was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Moreover, patients in the ORAL Surveillance study [ 19 ] were all over 50 years and had at least one major cardiovascular risk factor (e.g., smoking) that increases their neoplastic risk. In the rheumatoid arthritis population, malignancy is a leading cause of death [ 40 , 41 ], especially in patients not undergoing immunosuppressive therapy [ 42 ]. Nonetheless, this is also supported by our finding on RA indications, which is the only subgroup confirming the slightly increased risk of cancer in patients undergoing tofacitinib vs. anti-TNF.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients in the ORAL Surveillance study [ 19 ] were all over 50 years and had at least one major cardiovascular risk factor (e.g., smoking) that increases their neoplastic risk. In the rheumatoid arthritis population, malignancy is a leading cause of death [ 40 , 41 ], especially in patients not undergoing immunosuppressive therapy [ 42 ]. Nonetheless, this is also supported by our finding on RA indications, which is the only subgroup confirming the slightly increased risk of cancer in patients undergoing tofacitinib vs. anti-TNF.…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological surveys showed that the standardized incidence ratios of RA to develop cancer is 3.99 (95% CI = 3.40–4.65) ( Zhou et al, 2022 ), with cancer types ranging from different hematological malignancies which rank the first, to other various solid tumors, such as lung cancer, melanoma, cervical cancer etc. ( Zhang et al, 2022 ). Of note, lung adenocarcinoma (LUAD) was shown to be the most common lung cancers in AIDs ( Jacob et al, 2020 ) and pulmonary involvement is a common extraarticular manifestation of RA ( Sparks, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to young-onset RA (YORA), EORA patients are more likely to be male and seronegative for rheumatoid factor (RF) and anti-cyclic citrullinated protein (CCP) antibodies, and have markedly elevated C-reactive protein (CRP) levels and erythrocyte sedimentation rates, suggesting that EORA and YORA have a different pathophysiology [ 4 , 5 , 6 ]. In addition, patients with RA are at higher risk of developing malignancies, such as lymphomas, melanomas, and lung cancers, than healthy individuals [ 7 , 8 ]. Elderly patients with RA in particular are at high risk and often have a past or concurrent medical history of malignancy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%